ASYMPTOTICS OF THE MULTICLUSTER WAVE FUNCTIONS IN THE BINAR STRONG BIND CHANNELS. 2. RESULTS OF CACULATIONS - Afanas’eva, N.V.; Burkova, N.A.; Zhaksybekova, К.А.; Kabytaev, Ch.Z. (Recent Contributions to Physics, 2021)
The results of calculation for the asymptotic constants of the radial wave functions in the binary isobar-analogous 6He  p , 6Li  p , 6Li  n , 6Be  n cluster channels are present.